MATH ANXIETY AS A PREDICTOR OF MATH COMMUNICATION ABILITY ON SENIOR HIGH SCHOOL STUDENTS - Dinda Haniyah; Hikmatul Khusna (FKIP Universitas Muhammadiyah Tangerang, 2023)
Math anxiety is one of the aspects that plays a role in the form of talent that students have, so that if math anxiety can be controlled properly, so this aspect also has an important effect on students' math communication ability. This research aims to determine math anxiety as a predictor of the math communication ability of high school students. The sample in this research was at SMAN 10 Bekasi in semester 1 of the 2022-2023 academic year class XII. The research method used is the correlational research method. The sampling technique used is Simple Random Sampling. The sample taken was 58 students. The results of the research instrument test were obtained by testing the math communication ability test instrument as many as 5 questions and the math anxiety questionnaire instrument as many as 32 questions. This research have only examines one prediktor on math communication ability not only math anxiety many other factors affect math communication ability which has 91.2% and math anxiety as a predictor is also very small with 8.8% because it is effected by other factors So, students' communication ability cannot yet be said to be ideal. Because the average student does not have the math communication ability to ask questions and in solving math problems still depends on his friends. Meanwhile, students who have good grades are mostly due to often practicing questions at home and have the active to ask the teacher.